Estimating severe acute respiratory coronavirus virus 2 (SARS-CoV-2) seroprevalence from residual clinical blood samples, January–March 2021. Issue 1 (22nd September 2022) - Graciaa, Daniel S.; Verkerke, Hans P.; Guarner, Jeannette; Moldoveanu, Ana Maria; Cheedarla, Narayanaiah; Arthur, Connie M.; Maier, Cheryl L.; Neish, Andrew; Auld, Sara C.; Campbell, Angie; Gandhi, Neel R.; Roback, John D.; et al.
Abstract: We describe severe acute respiratory coronavirus virus 2 (SARS-CoV-2) IgG seroprevalence and antigenemia among patients at a medical center in January–March 2021 using residual clinical blood samples. The overall seroprevalences were 17% by infection and 16% by vaccination. Spent or residual samples are a feasible alternative for rapidly estimating seroprevalence or monitoring trends in infection and vaccination.